1952
DOI: 10.1107/s0365110x52001489
|View full text |Cite
|
Sign up to set email alerts
|

Optical and X-ray data on a group of isostructural uranium and plutonium compounds

Abstract: A group of isostructural compounds of hexavalent and tetravalent uranium and plutonium with tetraethyl and tetramethyl ammonium chloride (types----(R~N)2MC1 e and (R4N)2MO2C14) have been characterized by their optical properties and by X-ray diffraction analysis. Some errors in earlier data have been corrected and explained. The isostructuralism is maintained throughout the group, as evidenced by both crystal morphology and X-ray crystallography, although the space groups range from cubic to monoclinic. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0
3

Year Published

1976
1976
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 1 publication
5
31
0
3
Order By: Relevance
“…48,53 While the first reports of this salt indicated that the most stable phase was a tetragonal phase, the tetragonal phase was not ever able to be produced in this laboratory. 53 The preparation of a tetragonal phase is mentioned only among the earliest description of this salt and has never been subsequently reported.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…48,53 While the first reports of this salt indicated that the most stable phase was a tetragonal phase, the tetragonal phase was not ever able to be produced in this laboratory. 53 The preparation of a tetragonal phase is mentioned only among the earliest description of this salt and has never been subsequently reported.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…7 Even though there have been many experimental and computational studies of [U(f 1 )Cl 6 ] − in condensed phases, 1,8-16 the accurate account of the electronic structure of the [U(f 2 )Cl 6 ] 2− species has been challenging owing to the highly complex f 2 system and the perturbations caused by interactions with the countercations in crystal and solution phases. [17][18][19][20][21] Anion photoelectron spectroscopy (PES) is a powerful experimental technique to probe the ground and excited states of neutral species, through electron detachment from singly charged anions. We have developed PES techniques to study solution-phase species, both singly charged and multiply charged anions, in the gas phase using electrospray ionization a) J. Su and P. D. Dau contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…C Ftil3itz, with the SiF,, octahedra in a"ferro7' arrangement (34). Thc F I I I~I I I symmetry also appears to occur in a number of (Mc,N)?MX(, chlorides and brornides where M is a 5/' elcment (Th, Pa, U. Pu) and in thc high-temperature form of (Et4N)2PuC16 (35)(36)(37), while tlie corresponding (Et,N),MCI, and (Et,N)?PaBr(, at room temperature crystallize in Ftirt,rtn C Ftn3tr1 (36,37). (Et,N)?PaF(, is dimorphic, fcc and tetragonal, the latter form (isostructural with the U compound) probably related to Fti131n; (Et,N)ZPaOCIS is stated to be monoclinic.…”
Section: Dirner~sioils Of Tlre Siici Octahedramentioning
confidence: 99%